Field Mapping – A Field Method in Geography Lessons - Lindau, Anne-Kathrin (Journal of Geography Education, 2010)
The field mapping is an accepted method in geography science and school. The article is a report about the standard of knowledge of the field mapping. The focus of the literature is the description of the progress of the method field mapping. The mapping is suitable for all students from class 1 to 12. The field method is applicable to questions of the natural or human geography.